A quantitative evaluation of aerosol generation during supraglottic airway insertion and removal. (20th July 2021) - Shrimpton, A. J.; Gregson, F. K. A.; Brown, J. M.; Cook, T. M.; Bzdek, B. R.; Hamilton, F.; Reid, J. P.; Pickering, A. E.; ,
Summary: Many guidelines consider supraglottic airway use to be an aerosol‐generating procedure. This status requires increased levels of personal protective equipment, fallow time between cases and results in reduced operating theatre efficiency. Aerosol generation has never been quantitated during supraglottic airway use. To address this evidence gap, we conducted real‐time aerosol monitoring (0.3–10‐µm diameter) in ultraclean operating theatres during supraglottic airway insertion and removal. This showed very low background particle concentrations (median (IQR [range]) 1.6 (0–3.1 [0–4.0]) particles.l −1 ) against which the patient's tidal breathing produced a higher concentration of aerosol (4.0 (1.3–11.0 [0–44]) particles.l −1, p = 0.048). The average aerosol concentration detected during supraglottic airway insertion (1.3 (1.0–4.2 [0–6.2]) particles.l −1, n = 11), and removal (2.1 (0–17.5 [0–26.2]) particles.l −1, n = 12) was no different to tidal breathing (p = 0.31 and p = 0.84, respectively). Comparison of supraglottic airway insertion and removal with a volitional cough (104 (66–169 [33–326]), n = 27), demonstrated that supraglottic airway insertion/removal sequences produced <4% of the aerosol compared with a single cough (p < 0.001). A transient aerosol increase was recorded during one complicated supraglottic airway insertion (which initially failed to provide a patent airway). Detailed analysis of this event showed an atypical particle size distribution and we subsequently identified multiple sources of non‐respiratory aerosols that may be produced during airway management and can be considered as artefacts. These findings demonstrate supraglottic airway insertion/removal generates no more bio‐aerosol than breathing and far less than a cough. This should inform the design of infection prevention strategies for anaesthetists and operating theatre staff caring for patients managed with supraglottic airways.